Analysis on Implementation Elementary School Program in Strengthening Social Values - Sudarmin Sudarmin; Abdul Azis Muslimin; Rosleny B (Indonesian Journal of Primary Education, 2020)
This study aims to develop the implementation of a model school program by implementing an internal quality assurance system in meeting the achievement of eight national standards, and to develop routine activities of strengthening social values in students, as well as to determine the supporting and inhibiting factors of the school program model of strengthening social values in students. This research uses descriptive qualitative. Data were collected through interviews, observation and documentation. This study uses data analysis techniques, which consist of the stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the model school program carried out routine activities through learning, modeling, habituation, extracurricular activities, local wisdom culture, little doctor, and school health. The supporting and inhibiting factors are the achievement of the quality culture mapping of the Internal Quality Assurance System the strategic location of the school and adequate learning facilities, the readiness and support of educators and education staff, as well as the support of parents and the community , and the cooperation of the MOU (Memorandum Of Understanding), while the inhibiting factors are the limitations of teaching staff and education personnel to implement internal quality assurance system different student backgrounds, limited facilities and infrastructure, and there are still parents of students and the community who do not fully support the model school program. The conclusion of this study is that with a model school program, honest, disciplined, cooperation, tolerance,